Tanggung Jawab Perusahaan Terhadap Kebocoran Data Pribadi Dari Penggunaan Teknologi Robotic Process Automation (RPA) Menurut Hukum Positif di Indonesia - Yuni Zakira; Azheri, Busyra; Rosari, Anton (Lareh Law Review, 2025)
The constitutional basis regarding the importance of personal data protection is found in Article 28G paragraph (1) of the 1945 Constitution, providing a fundamental basis to guarantee the right to privacy, particularly the protection of personal data. This is due to the development of increasingly complex and large-scale technological innovations. As a result, information regarding personal data is much more likely to be accessed quickly and easily. Especially since the emergence of Robot Process Automation technology in all business fields. RPA is a software robot designed to perform repetitive tasks in processing data and information. Therefore, an enhancement of the security system of this technology is necessary. Thus, it becomes a challenge for businesses to prevent data breach cases such as the loss of personal data. Based on that issue, the problem will be formulated as follows. First, how is the legal regulation in Indonesia regarding the use of Robotic Process Automation (RPA) technology? Second, what is the company's responsibility in the event of data breaches from the use of Robotic Process Automation (RPA) technology? This research uses a normative juridical research type. The data used in this research are secondary data consisting of primary legal materials and secondary legal materials. Based on the research results, first, it was concluded that there are no specific regulations regarding robot process automation, but it can refer to the ITE Law, PDP Law, and Permenkominfo. Second, the company's liability for unlawful acts falls under vicarious liability. Keywords : Personal Data Protection, Responsibility, Robot Process Automation